Constraints of Workplace Experience Learning Implementation among Fashion Design TVET in Ghana - Phyllis Mensah; Harry Barton Essel; Akosua Tachie-Menson; Benjamin Tawiah; Aaron Daniel Akuteye (Formad English Foundation NTB Jakarta, 2026)
Workplace Experience Learning (WEL) programs are vital to Technical and Vocational Education because they enable students to apply classroom learning in real-world settings and develop entrepreneurial skills. In Ghana’s fashion design education context, WEL has gained significance; however, there is a paucity of empirical evidence on the effectiveness of these programs in enhancing students’ practical and entrepreneurial skills in technical universities. The study aimed to investigate the impact of WEL participation on the cultivation of entrepreneurial competencies among Higher National Diploma (HND) fashion design students in Ghana. The study examined the mediating role of placement activities, including mentorship, practical training, and supervision, and identified critical factors influencing the quality and outcomes of implementation. A sequential mixed-method design with an explanatory focus was utilised. Quantitative data were gathered from 250 students at four technical universities and analysed through regression and mediation models. To enhance interpretation of the findings, qualitative data from semi-structured interviews were analysed thematically using NVivo. The results indicated a substantial positive correlation between WEL participation and improvements in entrepreneurial competencies. Placement activities became important links due to weak ties between universities and industry, limited insurance coverage, limited family support, and communication problems. The study concludes that fortifying institutional coordination, augmenting support systems, and refining industry partnerships are essential to optimise WEL’s influence on fashion design education in Ghana.